Organizational Commitment of Vocational College Personnel in Thailand: A Confirmatory Factor Analysis - Saraviroj, Jitjan; Sisan, Boonchan; Ratanaolarn, Thanin (Journal of Technical Education and Training, 2024)
Issues of personnel commitment and retention challenge many industries and have significant impact on educational institutions. The objective of this study of organizational commitment among vocational college personnel in Thailand is to examine the construct validity of theoretical data with empirical data using confirmatory factor analysis. The population and sample were teachers and personnel working in vocational educational institutions in Thailand, totaling 640 teachers and personnel from 651 educational institutions, a sample size determined by synthesized criteria and using multi-stage random sampling. The research instrument was a 5-level rating scale questionnaire, validated by 5 experts, and tested to have a confidence value of 0.89. Data were examined to appraise initial consistency before further analysis and evaluation of the specified statistics and criteria. The research results found that the model is consistent with the empirical data through the specified criteria, with all variables having weights that pass the analysis criteria and being statistically significant. Based on the factor analysis, it can be confirmed that the 4 elements of superior leadership, entrepreneurial characteristics, organizational culture of learning, and organizational commitment, along with their associated components, comprise the structure of organizational commitment among vocational college personnel in Thailand.